Sociodemographic Correlates of Organized Sports Participation in a Sample of Middle School Students in China - Tao Ren; Jin Yan; Qiang Sun; Qiang Sun (Frontiers Media S.A., 2021)
Background: Organized sport participation (OSP) is considered as one method with the potential to increase overall physical activity (PA) levels in young people. It is essential to understand the correlates of OSP to inform future PA interventions.Purpose: This study aimed to explore the sociodemographic correlates of OSP among middle school students from the Nanjing City of China.Methods: A total of 7,097 adolescents (50.1% girls) aged 12-15 years from Nanjing, China, were recruited in this survey. Self-reported data on sex, grade, race, residence areas, proficient sport skills, and parental highest education were obtained. OSP was assessed by the question asked in the questionnaire on whether participants were involved in any "sports club or team" with the binary answer options of "yes" and "no," for statistical analysis purposes. Generalized linear models were used to determine the correlates of OSP.Results: Only 16.6% reported participating in any organized sport over the past whole year, while boys (OR = 1.34, 95% CI: 1.18-1.53) and 7th graders (OR = 1.40, 95% CI: 1.18-1.65) were more likely to participate in organized sport. Adolescents being Han ethnicity were less likely to either participate in organized sport (OR = 0.60, 95% CI: 0.40-0.92), or masterless (one or two) proficient sport skills [OR (one) = 0.27, 95%CI: 0.20-0.37; OR (two) = 0.43, 95% CI: 0.36-0.50]. Besides, both residence area and parental highest education were not significantly associated with OSP among the participating adolescents.Conclusion: The current study confirmed that only one-sixth of adolescents participate in the organized sport over the past year. At-risk population subgroups include girls, older adolescents, being Han ethnicity, and those proficient in fewer sport skills. Sex, grades, race, and proficient sport skills were significant correlates of OSP. School, community, and families need to provide more resources and support for disadvantaged populations in OSP.